2007
DOI: 10.1159/000112639
|View full text |Cite
|
Sign up to set email alerts
|

Increased Platelet Cholesterol and Decreased Percentage Volume of Platelets as a Secondary Risk Factor for Coronary Artery Disease

Abstract: Platelet hyperactivity is likely to contribute to the progression of atherogenesis and organized thrombus formation on vascular surfaces. The purpose of this study was to examine the effect of hypercholesterolemia on the cholesterol content of platelets, on platelet responsiveness and other platelet indices using platelets from 5 groups of age-matched subjects (n = 30 each), which includes healthy controls. All groups except controls had a high plasma lipid profile. While subjects in group I had only hyperlipi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

4
25
0

Year Published

2010
2010
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 31 publications
(29 citation statements)
references
References 62 publications
4
25
0
Order By: Relevance
“…It seems that PMA-induced aggregation is largely independent of Ca Finally, we demonstrated that the platelet aggregation and Ca 2+ mobilization induced by 0.1 unit/ml thrombin are significantly augmented in cholesterol-enriched rabbit platelets, in which cholesterol content was increased to 136% of control platelets. This result is in accordance with the observation that platelets from hypercholesterolemic humans and rabbits have increased cholesterol content (approximately 150% of control platelets) and hypersensitivity to platelet-aggregating agonists [3,21,25,28]. Together, our results suggested that the cholesterol content in platelets is critical to the regulation of platelet activation both in vitro and in vivo.…”
Section: Discussionsupporting
confidence: 92%
See 1 more Smart Citation
“…It seems that PMA-induced aggregation is largely independent of Ca Finally, we demonstrated that the platelet aggregation and Ca 2+ mobilization induced by 0.1 unit/ml thrombin are significantly augmented in cholesterol-enriched rabbit platelets, in which cholesterol content was increased to 136% of control platelets. This result is in accordance with the observation that platelets from hypercholesterolemic humans and rabbits have increased cholesterol content (approximately 150% of control platelets) and hypersensitivity to platelet-aggregating agonists [3,21,25,28]. Together, our results suggested that the cholesterol content in platelets is critical to the regulation of platelet activation both in vitro and in vivo.…”
Section: Discussionsupporting
confidence: 92%
“…Platelets from hypercholesterolemic humans have increased cholesterol content and hypersensitivity to endogenous aggregating agonists [9,21,25]. In familial hypercholesterolemic patients, cholesterol-lowering treatment with statin, an HMG-CoA reductase inhibitor, decreases the platelet cholesterol content and platelet sensitivity to the aggregating agonists such as ADP and collagen [9,17,18].…”
mentioning
confidence: 99%
“…Interestingly, red blood cell distribution width, a strong prognostic marker in cardiovascular disease, is positively associated with erythrocyte membrane cholesterol ( 53 ). Similarly, platelet cholesterol overload correlates with platelet activation and coronary artery disease ( 28 ).…”
Section: Discussionmentioning
confidence: 99%
“…Given this, the nature of the relationships in humans between serum cholesterol and both erythrocytes and platelets remain undefi ned outside of disease extremes, as does the broader relevance of these relationships to public health. Given that hypercholesterolemia, erythrocytosis, and thrombocytosis, as well as the membrane cholesterol content of both erythrocytes and platelets are all risk factors for cardiovascular disease (25)(26)(27)(28); there is a need for advancing our understanding of the underlying relationships between serum cholesterol and erythrocyte and platelet lineages in humans.…”
Section: Discussionmentioning
confidence: 99%
“…There is increasing evidence that cholesterol and lipoproteins affect platelet functions especially oxidized LDL. Animal models have shown that increased platelet cholesterol is due to the uptake of circulating cholesterol by megakaryocytes, which is then incorporated into future platelets 45) . Increased plasma and platelet cholesterol may lead to alterations in platelet membrane physiological processes in cigarette smokers since dysregulation of cholesterol synthesis and transport 46) with hypercholesterolemia is associated with increased platelet activity and hyperaggregability 47) .…”
Section: Discussionmentioning
confidence: 99%